Changes in intravenous and oral antimicrobial prescriptions during the coronavirus disease 2019 (COVID-19) pandemic: an experience at a tertiary-care center - Shutaro Murakami; Akane Takamatsu; Manabu Akazawa; Takao Goto; Toshiki Miwa; Yoshiyasu Terayama; Hitoshi Honda (Cambridge University Press, 2022)
Antimicrobial use during the coronavirus disease 2019 (COVID-19) pandemic at a tertiary-care center was analyzed using interrupted time-series analysis. Among intravenous antimicrobials, the use of azithromycin and third-generation cephalosporins significantly decreased during the current pandemic. Similarly, the use of oral antimicrobials, including azithromycin and fluoroquinolones, also decreased.